2018
DOI: 10.1111/vox.12664
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plasma transfusions on antithrombin levels after paediatric liver transplantation

Abstract: Plasma transfusions only marginally increase AT levels in children after LT. Therefore, prophylactic plasma transfusions probably do not seem to confer an advantage in the routine management of paediatric LT patients. Randomized controlled trials are needed to identify the optimal anticoagulation strategy in this specific population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…While these tests may indicate severe coagulopathy, they do not take concomitant alterations of the haemostasis system into account, including decreases in anti‐coagulant proteins, functional defects in fibrinogen, a compensatory increase in von Willebrand factor and enhanced platelet function . It has been suggested that, in patients with liver disease, a rebalanced haemostatic system is present that can easily be tipped towards bleeding or thrombosis .…”
Section: Discussionmentioning
confidence: 99%
“…While these tests may indicate severe coagulopathy, they do not take concomitant alterations of the haemostasis system into account, including decreases in anti‐coagulant proteins, functional defects in fibrinogen, a compensatory increase in von Willebrand factor and enhanced platelet function . It has been suggested that, in patients with liver disease, a rebalanced haemostatic system is present that can easily be tipped towards bleeding or thrombosis .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of plasma to correct INR values alone may falsely affect the prognostication of a child's condition and ability to list for transplant as scores typically use INR values in their prognostic models (51). Intraoperative plasma transfusions contribute to the procoagulant state, which increases the risk of thrombotic events (52) and acts as an independent risk factor for the development of patient and graft survival and postoperative complications, including acute kidney injury (53)(54)(55). An RCT comparing a restrictive with a liberal transfusion policy (to maintain a low or high central venous pressure) found that the restrictive policy led to a significant reduction in intraoperative blood loss and transfusion requirements (56,57).…”
Section: Indications Formentioning
confidence: 99%